Successful strategies for teaching undergraduate research - Deyrup, Marta Mestrovic; Uthup, Thomas (Scarecrow Press, Inc., 2013)
In this book the editors have brought together well-known educators from the fields of library science, communication, composition, and education to show you how to develop successful strategies for teaching undergraduates how to conduct basic research and write papers. The book fully explores current theories on pedagogy and provides practical demonstrations of how library instruction can reinforce critical thinking and set the groundwork in place for life-long learning.